2020
DOI: 10.1039/d0ra00818d
|View full text |Cite
|
Sign up to set email alerts
|

Featured properties of Li+-based battery anode: Li4Ti5O12

Abstract: A theoretical framework based on first-principles calculations is developed for the essential properties of the 3D ternary compound Li4Ti5O12, a Li+-based battery anode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…19 and 20. As for LTO and NTO, the electronic states have been investigated to design high-performance materials. [16][17][18][21][22][23][24][25][26][27][28][29][30][31] In a previous DFT study of LTO and newly discovered NTO, the electronic states and local atomic structures were examined. The O 2À anion in LTO and NTO can exibly move a distance from Ti, whereby it forms a coordinate bond with Ti and results in an analogous electronic state either for LTO or NTO with a local structural strain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 and 20. As for LTO and NTO, the electronic states have been investigated to design high-performance materials. [16][17][18][21][22][23][24][25][26][27][28][29][30][31] In a previous DFT study of LTO and newly discovered NTO, the electronic states and local atomic structures were examined. The O 2À anion in LTO and NTO can exibly move a distance from Ti, whereby it forms a coordinate bond with Ti and results in an analogous electronic state either for LTO or NTO with a local structural strain.…”
Section: Introductionmentioning
confidence: 99%
“…18 That is, the Li-substitution in the 16d sites is essential for either LTO or NTO from the viewpoint of crystallographic structure. Previous studies, [16][17][18][21][22][23][24][25][26][27][28][29] however, have not examined how Li-mixing in the 16d sites inuences the stability of the spinel framework and the relationship between the local structural strain and local energetic instability.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the cathode and anode systems of Li + -based batteries belong to a class of solidstate materials, such as the three-dimensional (3D) ternary LiFe/Co/NiO (Sakurai et al, 1997;Liu et al, 2002;Chen et al, 2014) and Li 4 Ti 5 O 12 /graphite compounds (Xiang et al, 2012;Nguyen et al, 2020), respectively, whereas conventional electrolytes belong to liquid states, which come with have potential security risks concerning volatilization, flammability and explosion. Recent experimental studies indicated that secondary batteries using inorganic solid electrolytes would be the ultimate batteries to resolve the safety issues (Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The previous numerical studies based on VASP simulations are sufficient in developing the theoretical framework for understanding the diversified material/physical/chemical phenomena. This framework has been successfully used to conduct systematic investigations of one-dimensional (1D) graphene nanoribbons (Lin et al, 2015b), two-dimensional (2D) graphene/silicene with chemical modifications (Lin et al, 2015a;Tran et al, 2018) and the three-dimensional (3D) ternary Li 4 Ti 5 O 12 compound (Nguyen et al, 2020). Through the delicate analysis, the diversified phenomena of the geometric, electronic and magnetic properties due to different dimensionalities, planar or buckled honeycomb lattices, layer numbers, stacking configurations, adatom chemisorptions, guest-atom substitutions and bulk properties of 3D materials can be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the theoretical framework, being based on the significant orbital hybridizations in chemical bonds 6,15,16 , is developed by examining the essential properties in the ternary lithium-based materials. This strategy is based on the accurate first-principles calculations on an optimal lattice symmetry with positiondependent chemical bondings, the atom-dominated band structure at different energy ranges, the spatial charge densities due to various orbitals, and the atom-and orbital-projected van Hove singularities related to orbital overlaps.…”
mentioning
confidence: 99%